The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/16549716.2022.2054110
|View full text |Cite
|
Sign up to set email alerts
|

A lack of reproductive agency in facility-based births makes home births a first choice regardless of potential risks and medical needs—a qualitative study among multiparous women in Somaliland

Abstract: Background Around 20% of births in Somaliland take place at health facilities staffed by trained healthcare professionals; 80% take place at home assisted by Traditional Birth Attendants (TBAs) with no formal training. There has been no research into women’s choice of place of birth. Objective In this study, we explore multipara women’s needs and preferences when choosing the place of birth. Method An explorative qualitative study using indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Our findings are in concordance with previous literature that suggests that women value a supportive and familiar environment during childbirth. A recent study in Somaliland has shown that home births are believed to make it easier to manage women's concerns about privacy and psychosocial support during childbirth [20]. Similarly, an interpretive synthesis of literature relating the concepts of "place" and "space" to childbirth suggests that providing women with a familiar and home-like environment can increase feelings of comfort, control, and autonomy during labor and delivery, which plays a significant role in shaping positive experiences with childbirth [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in concordance with previous literature that suggests that women value a supportive and familiar environment during childbirth. A recent study in Somaliland has shown that home births are believed to make it easier to manage women's concerns about privacy and psychosocial support during childbirth [20]. Similarly, an interpretive synthesis of literature relating the concepts of "place" and "space" to childbirth suggests that providing women with a familiar and home-like environment can increase feelings of comfort, control, and autonomy during labor and delivery, which plays a significant role in shaping positive experiences with childbirth [21].…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown that at HGH, around 70% of women gave birth without complications and that most women bypassed the primary healthcare level (self‐referred) during the study period. In Somaliland, most women (80%) deliver at home supported by a traditional birth attendant and the rest deliver at a healthcare facility 20 . This indicates that a considerable proportion of women with normal pregnancies and uncomplicated deliveries attend the referral hospital instead of a primary healthcare center, resulting in overcrowding and suboptimal care.…”
Section: Discussionmentioning
confidence: 99%
“…In Somaliland, most women (80%) deliver at home supported by a traditional birth attendant and the rest deliver at a healthcare facility. 20 This indicates that a considerable proportion of women with normal pregnancies and uncomplicated deliveries attend the referral hospital instead of a primary healthcare center, resulting in overcrowding and suboptimal care. A recent qualitative study among multiparous women in Somaliland found that a lack of reproductive agency in facility‐based births makes home births their first choice, regardless of medical need.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations